In Bilinguals' Hands: Identification of Bilingual, Preverbal Infants at Risk for Language Delay - Lüke, Carina; Ritterfeld, Ute; Liszkowski, Ulf (Frontiers in Pediatrics, 2022)
Studies with monolingual infants show that the gestural behavior of one- to two-year-olds is a strong predictor for later language competencies and, more specifically, that the absence of index-finger pointing at 12 months seems to be a valid indicator for risk of language delay (LD). In this study a lack of index-finger pointing at 12 months was utilized as diagnostic criterion to identity infants with a high risk for LD at 24 months in a sample of 42 infants growing up bilingually. Results confirm earlier findings from monolinguals showing that 12-month-olds who point with the extended index finger have an advanced language status at 24 months and are less likely language delayed than infants who only point with the whole hand and do not produce index-finger points at 12 months.